DEVELOPMENT OF ANTIBODY TO RALSTONIA SOLANACEARUM AND ITS APPLICATION FOR DETECTION OF BACTERIAL WILT - YADI SURYADI (BIOTROPIA, 2009)
The serological assay for  the detection of  bacterial wilt caused by Ralstonia  solanacearum  RSwas able to provide  information regarding the presence of  the pathogen  in plant materials Theresearch is was aimed to develop polyclonal antibody PAb for RS detection Bacterial wholecells of  RS isolates mixed with glutaraldehyde were used to immunize New Zealand femalewhite  rabbit The  titre of  antibody  in culture supernatant was 1 1024 The PAb developed  froma ground nut RS  isolates reacted with  infected plant samples from various  locations It was ableto detect RS antigen of  crude extract and pure cultures from tomato and potato plant samples45 using dot blot ELISA however the minimum detectable concentration of  RS antigen was 10cellsml The PAb obtained in this study is sensitive enough to detect RS isolates in routineserological assayKey words  Bacterial wilt Ralstonia  solanacearum antibody dot blot ELISA